Living Law Dalam KUHP: Suatu Gagasan Menginventarisasi Kompilasi Hukum Adat - Daffa Ladro Kusworo; Maghfira Nur Khaliza Fauzi (Jurist-Diction, 2024)
AbstractThe living law provisions contained in Article 2 Paragraph 1 of the KUHP make customary law to determine whether person can be convicted as balance of national legal system. However, problem lies in inclusion customary offenses in Regional Regulations which are contradictory dynamically moving customary law. However, there is a contradiction in the issue of whether it expands the principle of legality, or violates the principle of legality itself. This study uses normative juridical method that refers to legislation and conceptual approach based on doctrine legal positivism, as well as literature studies from various research literatures, books, journals, and other legal materials. The results show that design follow-up living law in KUHP is more appropriate to do with inventory Compilation Customary Law as convenience for law enforcement officers, especially judges resolve cases by finding value of justice, as well as making it easier for legislators to find actions that will be regulated in regulations. future legislation (ius constituendum).Keywords: Compilation of Customary Law; Living Law; KUHP. AbstrakKetentuan living law yang termuat dalam Pasal 2 Ayat 1 KUHP menjadikan hukum adat dapat menentukan seseorang dapat dipidana sebagai keseimbangan sistem hukum nasional. Namun persoalan terdapat kontradiksinya yang apakah memperluas asas legalitas, atau menyalahi dari asas legalitas itu sendiri. Penelitian ini menggunakan metode yuridis normatif yang mengacu pada perundang-undangan dan pendekatan konseptual yang didasari atas doktrin positivisme hukum, serta studi kepustakan dari berbagai literatur hasil penelitian, buku, jurnal, dan bahan hukum lainnya. Hasil penelitian menunjukkan bahwa desain tindak lanjut living law dalam KUHP lebih tepat dilakukan dengan inventarisasi Kompilasi Hukum Adat sebagai kemudahan bagi aparat penegak hukum, terutama hakim untuk menyelesaikan perkara dengan menggali nilai-nilai keadilan, serta memudahkan pembentuk undang-undang untuk menemukan perbuatan yang akan diatur dalam peraturan perundang undangan di masa yang akan datang (ius constituendum).Kata Kunci: Kompilasi Hukum Adat; Living Law; KUHP.